Method for obtaining high-performance supercapacitor negative electrode material by introducing dislocation and oxygen vacancy

By introducing dislocations and oxygen vacancies into the iron-based oxide material, Ni3Fe@Fe3O4 nanochain structure was prepared, which solved the problems of low conductivity, poor cycling stability and expansion and contraction of the material, and significantly improved the performance of the supercapacitor.

CN119673680APending Publication Date: 2025-03-21JILIN UNIVERSITY
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411708430.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

Iron-based oxide materials have problems with low conductivity, poor cycling stability and expansion and contraction in supercapacitors, limiting their efficiency and service life in high power applications.

Method used

By introducing dislocations and oxygen vacancy, Ni3Fe@Fe3O4 nanochain structure was prepared by the preparation method of nickel source, iron source and complexing agent and magnetic field-assisted hydrazine hydrate reduction method to improve the conductivity and cyclic stability of the material.

Benefits of technology

The charge transfer efficiency of the negative electrode material of the supercapacitor is significantly improved, the number of active sites is increased, the volume expansion during the charge and discharge process is suppressed, and the overall energy storage capacity and cycling stability are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119673680A_ABST
    Figure CN119673680A_ABST
Patent Text Reader

Abstract

The invention discloses a method for obtaining a high-performance supercapacitor negative electrode material by introducing dislocation and oxygen vacancy, and belongs to the technical field of supercapacitor and battery electrode materials. A hydrazine hydrate reduction method under the assistance of a magnetic field is adopted, Ni3Fe nanospheres generated by a magnetic field induction reaction are linearly arranged into a nano chain along the magnetic field, and an anoxic environment is created on a reaction interface by regulating and controlling the proportion and temperature of argon and oxygen, so that the final reaction product Fe3O4 realizes introduction of oxygen vacancies due to insufficient oxygen in the reduction process; through temperature control, the rapid reduction process of hydrazine hydrate is realized, atoms are difficult to arrange into a perfect crystal structure, and due to the fact that the Fe reduction process is accompanied with the Fe3O4 conversion process, more structural disorder exists in Fe3O4, a large amount of blade dislocation is introduced, and finally the supercapacitor negative electrode material rich in dislocation Ni3Fe and Fe3O4 is synthesized. The electrochemical performance of the electrode material is improved on the premise that electrode components are not changed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0002] The invention relates to the technical field of supercapacitor and battery electrode materials. Background Art

[0004] Supercapacitors have the advantages of high power density, long cycle life and fast charging. They can release a large amount of energy in a short period of time, charge quickly, and can be used hundreds of thousands of times with almost no aging problems. Their high energy efficiency and environmental protection characteristics make them widely used in electric vehicles, energy storage systems and portable devices. However, due to the low capacity of commonly used capacitor activated carbon negative electrode materials, the energy density of supercapacitors has reached a bottleneck and cannot be further improved. In addition, the types of supercapacitor negative electrode materials available are limited. Therefore, there is an urgent need to develop high-performance negative electrode materials, combined with effective modification strategies, to make up for the shortcomings of capacitor activated carbon negative electrode materials, and match them with high-capacity positive electrode materials to obtain high-energy density supercapacitors.

[0005] Iron-based oxide negative electrode materials, such as Fe2O3, Fe3O4 and FeOOH, are ideal negative electrode materials for supercapacitors due to their high theoretical specific capacity and potential window, and are considered to be new negative electrode materials that can replace traditional carbon negative electrode materials. These materials have become a research hotspot for supercapacitor negative electrode materials due to their abundant natural reserves, environmental friendliness and low cost, and are also widely used in water treatment, environmental monitoring, optoelectronic devices and other fields.

[0006] Although iron-based oxides show great advantages as supercapacitor negative electrode materials, the materials themselves still face the following problems: (1) Low electrical conductivity: Iron-based oxide materials have low electrical conductivity, which limits their efficiency in high-power applications, especially in situations of rapid charging and discharging. Therefore, they need to be compounded with high-conductivity materials to improve the overall conductivity and inhibit the aggregation of nanoparticles during the cycle. The introduction of oxygen vacancies can also effectively increase the electrical conductivity of electrode materials and improve the charge transfer efficiency.

[0007] (2) Poor cycle stability: Iron-based oxide materials are prone to capacity decay during repeated charge and discharge, resulting in performance degradation during long-term use. Especially in supercapacitors, iron-based oxide materials may undergo structural changes, and effective modification measures are urgently needed to inhibit the irreversible phase change of iron-based oxides. Dislocations can effectively hinder the movement of the phase change interface and inhibit this irreversible phase change.

[0008] (3) Expansion and contraction problems: Iron-based oxide materials may expand and contract in volume during the charge and discharge process, which can cause mechanical damage to the material and electrode shedding, affecting its service life. The introduction of dislocations can form an interaction force when the material undergoes expansion or contraction, which can effectively control and alleviate this expansion effect.

[0009] In summary, from the perspective of improving the conductivity and cycle stability of iron-based oxide materials, effective modification methods are urgently needed to improve their preparation methods without changing the composition, so as to obtain supercapacitor negative electrode materials with high capacity, high rate performance and stable structure. Summary of the invention

[0011] In order to solve the above problems, the present invention provides a method for obtaining a high-performance supercapacitor negative electrode material by introducing dislocations and oxygen vacancies. The technical solution adopted is as follows: A method for obtaining a high-performance supercapacitor negative electrode material by introducing dislocations and oxygen vacancies, the specific steps being: S1. Reactant composition ratio and pretreatment: S1.1. Select nickel source, iron source and complexing agent, and prepare mixed solution: The nickel source is anhydrous powdered nickel chloride NiCl2·6H2O; the iron source is anhydrous powdered ferrous sulfate FeSO4·7H2O; the complexing agent is white crystalline powdered sodium citrate C6H5Na3O7·2H2O; the method for preparing the complex solution is to place 0.523-1.046 g of nickel chloride powder, 0.611-1.223 g of ferrous sulfate powder and 0.441-1.323 g of sodium citrate powder in a glass container under dry and dust-free environment conditions, add 30 mL of ultrapure water to dissolve them, place the base liquid on a magnetic stirrer and use a rotor to stir it evenly to form a mixed solution for standby use, and continue stirring during the standby period.

[0012] S1.2, prepare reducing agent solution: The reducing agent is transparent liquid hydrazine hydrate N2H4·H2O. The reducing agent solution is prepared by adding 1-5 mL of hydrazine hydrate into 25-29 mL of ultrapure water to form a 2.6-13.3 vol% hydrazine hydrate reducing agent solution. The reducing agent solution is placed on a magnetic stirrer and stirred by a rotor to form a uniform reducing agent solution for standby use, and ultrasonic stirring is continued during the standby period.

[0013] S1.3, pretreatment of the mixed solution and the reducing agent solution before reaction; The pretreatment includes adjusting the pH of the mixed solution and the reducing agent solution, deoxygenating and preheating; Among them, the pH adjustment method is to add 6 M potassium hydroxide (KOH) solution dropwise into the solution and repeatedly measure its pH value to adjust the pH value to 11-14; the deoxygenation method is to use argon gas to purge the mixed solution and the reducing agent solution for 0.25-1.5 h to remove the dissolved oxygen in the solution; the preheating method is to place the two solutions in a water bath and heat them to 60-100 ° C to preheat the solution.

[0014] S1.4, the mixed solution is mixed with the reducing agent solution: In a dry and dust-free environment, quickly mix the mixed solution and the reducing agent solution in a beaker, stir quickly, add to the reaction device and seal.

[0015] S2. Material preparation with controlled dislocation and oxygen vacancy introduction: S2.1. Design of reaction device: The reaction generating device comprises an adjustable magnetic field generator, a water bath pot controlled by a constant temperature, an oxygen concentration tester, a reaction container, a sealing plug, an argon cylinder, an oxygen cylinder and a gas circuit system; The reaction container is placed in a thermostatically controlled water bath, and a sealing plug is used to seal the reaction container; an argon cylinder and an oxygen cylinder are used to introduce argon and oxygen into the reaction container through a gas path system, and an oxygen concentration tester is used to detect the oxygen concentration at the reaction interface in the reaction container. When the oxygen concentration at the interface reaches a predetermined value, the introduction of argon and oxygen is stopped and the reaction container is kept sealed; The magnetic field generator is used to provide a uniform magnetic field with magnetic lines parallel to the axis of the beaker and perpendicular to the surface of the solution in the reaction container, and the adjustable range is 0-1000 Gs; S2.2, Reaction environment parameter setting: The magnetic field generator provides a uniform magnetic field with a magnetic field strength B of 100-500 Gs, the temperature T of the constant temperature water bath is 60-100°C, and the interface gas phase is a mixed gas of argon and oxygen, wherein the volume percentage concentration of oxygen is 1-30%; S2.3, synthesis time: The synthesis time t is 0.5-3 h.

[0016] Post-treatment of S3 and Ni3Fe@Fe3O4 nanochains S3.1. Impurity cleaning: remove the magnetic field, centrifuge the product, and wash the product with water and ethanol respectively; S3.2. Drying process setting: The cleaned reaction product is placed in a vacuum drying oven and dried at 60-100 °C for 4-15 h to obtain Ni3Fe@Fe3O4 core-shell structure nanochains.

[0017] The beneficial effects of the present invention are: (1) Carbon materials such as carbon nanotubes, graphene, and capacitor activated carbon are used as conductive cores. The synthesis process is complex and requires high temperatures, which is not in line with the low-carbon and environmentally friendly policy advocated by the country. Ni3Fe, as a conductive core, has better conductivity. The preparation method of Ni3Fe@Fe3O4 negative electrode material is relatively simple and does not require high-temperature calcination.

[0018] (2) The present invention simultaneously introduces dislocations and oxygen vacancies into the nanomaterial, and the symbiosis of the two significantly improves the charge transfer efficiency of the electrode material and increases the number of active sites.

[0019] (3) The present invention inhibits volume expansion during the charge and discharge process by introducing dislocations and oxygen vacancies, inhibits irreversible transformations in the electrode, and is beneficial to improving the overall energy storage capacity and cycle stability of the supercapacitor. By increasing the degree of disorder to modify the electrode material, the electrode material can be modified without changing the electrode composition.

[0020] (4) It makes up for the defects of activated carbon as a negative electrode device, namely low overall energy density and poor actual energy storage capacity.

[0021] (5) The method of introducing dislocations and oxygen vacancies of the present invention uses relatively abundant, green and low-cost raw materials; the present invention plans the preparation process and technology by matching the proportions of the solute solution components in the complex solution, sets a constant temperature T and magnetic field, and uses a magnetic field-assisted hydrazine hydrate reduction method for one-step molding. The process is simple and can produce supercapacitor negative electrode materials with high active sites, high conductivity and high capacity, which has the potential for industrialization and market application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] The drawings described herein are used to provide further understanding of the present invention and constitute a part of this application. The illustrative examples of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.

[0023] Figure 1 Schematic diagram of the reaction device for obtaining high-performance negative electrode Ni3Fe@Fe3O4 material by introducing dislocations and oxygen vacancies in the present invention; Figure 2 The Ni-Fe alloy phase diagram in the preparation principle of the high-performance negative electrode Ni3Fe@Fe3O4 material obtained by introducing dislocations and oxygen vacancies in the present invention (data source: Thermo-Calc software); Figure 3 The Gibbs energy of each phase in the reduction process of the high-performance negative electrode Ni3Fe@e3O4 material obtained by introducing dislocations and oxygen vacancies in the present invention (data source: Thermo-Calc software); Figure 4The high-performance negative electrode Ni3Fe@Fe3O4 material obtained by introducing dislocations and oxygen vacancies in the present invention is adsorbed by a magnet; Figure 5 The X-ray diffraction pattern of the high-performance negative electrode Ni3Fe@Fe3O4 material obtained by introducing dislocations and oxygen vacancies in the present invention; Figure 6 The scanning electron microscope photograph of the high-performance negative electrode Ni3Fe@Fe3O4 material obtained by introducing dislocations and oxygen vacancies in the present invention, with a magnification of 25,000 times; Figure 7 The high-resolution photo of the core-shell interface of the high-performance negative electrode Ni3Fe@Fe3O4 material obtained by introducing dislocations and oxygen vacancies in the present invention is magnified 820,000 times; Figure 8 A high-resolution photograph of the outer shell of the high-performance negative electrode Ni3Fe@Fe3O4 material obtained by introducing dislocations and oxygen vacancies in the present invention, with a magnification of 820,000 times; Fig. 9 A high-resolution photograph of the outer shell of the high-performance negative electrode Ni3Fe@Fe3O4 material obtained by introducing dislocations and oxygen vacancies in the present invention shows a local enlarged picture of the dislocation and oxygen vacancy coexistence area. The lower left corner is the FFT map of the area, and the lower right corner is the plane crystal model of the area; Fig.10 The high-resolution O1s XPS spectrum of the high-performance negative electrode Ni3Fe@Fe3O4 material obtained by introducing dislocations and oxygen vacancies in the present invention; Fig.11 The high-performance negative electrode Ni3Fe@Fe3O4 material obtained by introducing dislocations and oxygen vacancies at 1A g -1 -20A g -1 Constant current charge and discharge curves under current density; Fig.12 The preferred example of the high-performance negative electrode material obtained by introducing dislocations and oxygen vacancies in the present invention is comparable to commercial carbon (AC) at 1A g -1 -20A g -1 Comparison of mass specific capacity under current density; Fig.13 The high-performance negative electrode Ni3Fe@Fe3O4 material obtained by introducing dislocations and oxygen vacancies at 20 A g -1 Capacity retention curve of the cycle stability test under . DETAILED DESCRIPTION

[0025] The following will be combined with the accompanying drawings to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0026] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the present invention is further described in detail below with reference to the accompanying drawings and specific embodiments.

[0027] See also Figure 1 As shown, by using the device shown in the figure, Ni3Fe@Fe3O4 core-shell structure nanochains are synthesized in one step, while controlling various reaction parameters to achieve controllable introduction of dislocations and oxygen vacancies to obtain high-performance supercapacitor negative electrode materials. It is creatively proposed to introduce dislocations and oxygen vacancies when synthesizing nanomaterials to modify the electrode materials at the atomic and surface levels, provide a large number of active sites, and obtain excellent single electrode capacity, rate and cycle stability; Ni3Fe@Fe3O4 anode material is synthesized in a one-step method, the synthesis process is simple, and the preparation process is simplified.

[0028] See also Figure 2 , Figure 3 As shown in the simulation results of Thermo-Calc software, under specific conditions, when the nickel content is between 63-85%, the Ni3Fe intermetallic compound phase can be formed. Further calculations by calculating the Gibbs energy of each phase at 80°C show that with the change of nickel content, only the products with α-Fe phase and Ni3Fe phase have ΔG < 0. This indicates that at 80°C, the α-Fe phase and Ni3Fe phase can form spontaneously. In addition, the Ni3Fe phase exhibits a lower Gibbs free energy, indicating higher thermodynamic and kinetic stability. Therefore, Ni in solution 2+ and Fe 2+ The ions rapidly nucleate and grow into Ni3Fe nanospheres. In the subsequent synthesis process, the synthetic environment is controlled to control the introduction of dislocations and oxygen vacancies to obtain high-performance supercapacitor negative electrode materials. It is creatively proposed to introduce dislocations and oxygen vacancies when synthesizing nanomaterials to modify the electrode materials at the atomic and surface levels, providing a large number of active sites and obtaining excellent single electrode capacity, rate and cycle stability; the Ni3Fe@Fe3O4 anode material is synthesized by a one-step method, the synthesis process is simple, and the preparation process is simplified.

[0029] In this embodiment, a method for obtaining a high-performance supercapacitor negative electrode material by introducing dislocations and oxygen vacancies is provided, and the steps are as follows: S1. Reactant composition ratio and pretreatment: S1.1. Select nickel source, iron source and complexing agent, and prepare mixed solution: The nickel source is anhydrous powdered nickel chloride NiCl2·6H2O of standard purity (CAS No.: 7791-20-0); the iron source is anhydrous powdered ferrous sulfate FeSO4·7H2O of standard purity (CAS No.: 7720-78-7); the complexing agent is white crystalline powdered sodium citrate C6H5Na3O7·2H2O of standard purity (CAS No.: 6132-04-3); The mixed solution preparation method is as follows: 0.7843 g of nickel chloride powder, 0.9174 g of ferrous sulfate powder and 0.97 g of sodium citrate powder are placed in a glass container under dry and dust-free environment conditions, 30 mL of ultrapure water is added to dissolve them, and the base liquid is placed on a magnetic stirrer and stirred by a rotor to mix them evenly to form a mixed solution for standby use, and stirring is continued during the standby period.

[0030] S1.2, prepare reducing agent solution: The reducing agent is transparent liquid hydrazine hydrate N2H4·H2O; the reducing agent solution is prepared by adding 4 mL of hydrazine hydrate into 26 mL of ultrapure water to prepare a 10.67 vol% hydrazine hydrate reducing agent solution, placing the reducing agent solution on a magnetic stirrer, stirring with a rotor to form a uniform reducing agent solution for standby use, and continuously performing ultrasonic stirring during the standby period.

[0031] S1.3. Pretreatment of mixed solution and reducing agent solution before reaction: The pretreatment includes adjusting the pH of the mixed solution and the reducing agent solution, deoxygenating and preheating; Among them, the pH adjustment method is to add 6 M potassium hydroxide (KOH) solution dropwise into the solution and repeatedly measure its pH value to adjust the pH value to 13.3; the deoxygenation method is to use argon gas to purge the mixed solution and the reducing agent solution for 0.5h to remove the dissolved oxygen in the solution; the preheating method is to place the two solutions in a water bath and heat them to 80°C to preheat the solution.

[0032] S1.4, the mixed solution is mixed with the reducing agent solution: In a dry and dust-free environment, quickly mix the mixed solution and the reducing agent solution in a beaker, stir quickly, add to the reaction device and seal.

[0033] S2. Material preparation with controlled dislocations and oxygen vacancies S2.1, design of reaction device; The reaction generating device comprises an adjustable magnetic field generator, a water bath pot controlled by a constant temperature, an oxygen concentration tester, a reaction container, a sealing plug, an argon cylinder, an oxygen cylinder and a gas circuit system; The reaction container is placed in a thermostatically controlled water bath, and a sealing plug is used to seal the reaction container; an argon cylinder and an oxygen cylinder are used to introduce argon and oxygen into the reaction container through a gas path system, and an oxygen concentration tester is used to detect the oxygen concentration at the reaction interface in the reaction container. When the oxygen concentration at the interface reaches a predetermined value, the introduction of argon and oxygen is stopped and the reaction container is kept sealed; The magnetic field generator is used to provide a uniform magnetic field with magnetic lines parallel to the axis of the beaker and perpendicular to the surface of the solution in the reaction container, and the adjustable range is 0-1000 Gs; S2.2, Reaction environment parameter setting: The magnetic field generator provides a uniform magnetic field with a magnetic field strength B of 300 Gs, the temperature T of the constant temperature water bath is 80°C, and the interface gas phase is a mixed gas of argon and oxygen, in which the volume percentage concentration of oxygen is 20%; S2.3. Synthesis time: The synthesis time t is 1 h.

[0034] Since Ni3Fe has lower Gibbs free energy and higher thermodynamic and kinetic stability, the nickel source, cobalt source and reducing agent react first, and the reaction speed is extremely fast. The specific chemical equation is: 3Ni(II) + Fe(II) + 2N2H4+ 8OH - → Ni3Fe + 2N2 + 8H2O After the nickel source reacts completely and there are no nickel ions in the solution, the chemical equation for the reaction is: 2Fe(II) + N2H4 + 4OH - → 2Fe + N2 + 4H2O The material synthesis method is the hydrazine hydrate reduction method assisted by a magnetic field. Since the reaction product Ni3Fe has soft magnetic properties, the magnetic particles are easily arranged in order under the action of the uniform magnetic field generated by the magnetic field generator, which promotes the nucleation of Ni3Fe nanospheres, which will be linearly arranged along the magnetic field to form 1D nanochains with high conductivity. While improving the overall conductivity and the number of active sites, it provides a high specific surface area for the subsequent coating process. The stronger the magnetic field intensity, the higher the length of the linear nanochain.

[0035] Subsequently, all Ni 2+ After being consumed, the remaining Fe 2+Reacting with hydrazine hydrate, fine nanosheets covering the Ni3Fe chains are formed, forming a core-shell structure, and the surface of the nanochain becomes rough. Since oxygen is not specifically excluded during the reaction process and the growth process of Fe is slow, the reaction process inevitably undergoes oxidation, resulting in the oxidation of the Fe shell to Fe3O4. Affected by the buoyancy of the N2 bubbles and the magnetic force generated by the magnetic field, the nanochain moves up and down repeatedly. The movement of the nanochain is hindered by the adjacent nanochains, so a large number of physical contacts and metal joints are generated between the nanowires due to the van der Waals force and magnetic interaction. This interaction causes the chain to gradually become longer. When the length limit is reached, the magnetic attraction on the nanochain exceeds the buoyancy of the N2 bubbles, causing all the chains to gather at the bottom of the beaker, and finally synthesizing the Ni3Fe@Fe3O4 core-shell structure nanochain. In the control experiment without a magnetic field, the nanoparticles tend to aggregate into clusters rather than form chains. With the increase of the nickel proportion, the length of the nanochain changes significantly. When the feed ratio is Ni: Fe=2: 1, the length of the nanochain reaches the millimeter level.

[0036] The present invention regulates the ratio of argon and oxygen during the reaction process and monitors it through an oxygen concentration tester. When the interface oxygen concentration reaches a predetermined value, ventilation is stopped and the device is kept sealed, and dissolved oxygen exists in the solution. In the present invention, the reaction of hydrazine hydrate and metal ions produces a large amount of N2 bubbles, which reduces the solubility of oxygen in water. In addition, the solubility of oxygen decreases with increasing temperature, and the water bath heating environment further reduces the solubility of oxygen, thereby forming an oxygen-deficient environment. Since the Gibbs free energy of Fe is higher than that of Ni3Fe, the reductant reacts only slowly with the iron source Fe(II). Although oxidation is inevitable during the growth process after Fe nucleation, the insufficient availability of oxygen prevents Fe from being formed. 2+ Completely converted to Fe 3+ , so the final reaction product is Fe3O4, and due to the lack of oxygen in the reduction process, the introduction of oxygen vacancies is achieved. The corresponding chemical reaction equation is: 2Fe + 2O2 + 2H2O →2Fe(OH)2 4Fe(OH)2+ O2+ 2H2O → 4Fe(OH)3 Fe(OH)2+ 2Fe(OH)3→O V -Fe3O4+4H2O In the above reaction, when the oxygen concentration is too low, the reduced Fe cannot be further converted into active substances, which reduces the capacity performance of the electrode material. When the oxygen concentration is too high, the reduced Fe is completely converted into structurally unstable Fe2O3, resulting in decreased material stability. The interface environment can effectively control the composition of the reaction products while achieving controllable introduction of oxygen vacancies by properly controlling the oxygen concentration of the interface environment.

[0037] During the growth process after Fe nucleation, the crystal growth accompanied by the oxidation process increases the proportion of grain boundaries in the particles. The atoms at the grain boundaries are usually more disordered, and the high-density grain boundaries and defects promote the formation and propagation of dislocations. The thermostatically controlled water bath provides a constant temperature environment for the reaction. The reaction rate is positively correlated with the temperature. By controlling the temperature, the reaction rate is adjusted. The rapid reduction process of hydrazine hydrate does not have enough time for the atoms to arrange into a perfect crystal structure. Therefore, there is more structural disorder in the reduction product Fe3O4 compared to Ni3Fe, and a large number of edge dislocations are introduced, and finally the dislocation-rich Ni3Fe@Fe3O4 supercapacitor negative electrode material is synthesized.

[0038] Through the above mechanism, dislocations and oxygen vacancies in nanomaterials can be artificially introduced, and the reaction products and oxygen vacancy content can be controlled by the oxygen content in the reaction device; the reaction rate can be controlled by the reducing agent concentration and the heating temperature to achieve control over the introduction of dislocations.

[0039] Post-treatment of S3 and Ni3Fe@Fe3O4 nanochains S3.1 Impurity cleaning: The magnetic field was removed, the product was centrifuged, and washed three times with water and ethanol respectively; S3.2 Drying: The cleaned reaction product was placed in a vacuum drying oven and dried at 60°C for 8 h to obtain Ni3Fe@Fe3O4 core-shell structured nanochains.

[0040] See also Figure 4 The photo shown is of the Ni3Fe@Fe3O4 nanochain magnet being attracted by a magnet. Due to its ability to be attracted by a magnet, the nanomaterial can be synthesized with the assistance of a magnetic field.

[0041] See also Figure 5 As shown, the XRD pattern proves that the Ni3Fe@Fe3O4 negative electrode material was successfully prepared. All strong diffraction peaks are attributed to Ni3Fe, while all weak diffraction peaks are attributed to Fe3O4. The low and broad peaks of the weak diffraction peaks, accompanied by a small angle shift, confirm the reduction in crystallinity caused by the introduction of a large number of defects.

[0042] See also Figure 6 As shown, the Ni3Fe@Fe3O4 negative electrode material prepared by one-step method has a typical core-shell structure and 1D chain characteristics. The diameter of the nanochain is about 100 nanometers. Under the condition of having the same number and diameter of metal particles, compared with 2D and 3D network structures, the contact area between particles inside 1D nanowires is smaller, which gives nickel nanowires a higher number of active sites.

[0043] See also Figure 7-Figure 9As shown in the figure, the transmission high-resolution photograph at the core-shell interface shows that there are a large number of mismatch dislocations in the composite part of Ni3Fe and Fe3O4 due to the mismatch of the lattice fringes of the two crystal directions; in the Fe3O4 shell, there are mainly areas with only oxygen vacancies and areas where oxygen vacancies and dislocations coexist. The FFT map of this area confirms the existence of a large number of dislocations in this area. Through the analysis of the planar crystal model of this area, it can be observed that dislocations and oxygen vacancies have high-density defects and lattice irregularities. Therefore, it can significantly affect the electron and ion transport characteristics, provide a large number of active sites, improve the electrode / electrolyte interface reaction, and inhibit the volume expansion during the cycle process, realizing the modification of the electrode material without changing the material composition.

[0044] See also Fig.10 As shown, the high-resolution O1s spectrum of the Ni3Fe@Fe3O4 material confirmed that 21.46% of oxygen vacancies were introduced into the material. The introduction of oxygen vacancies increased the number of active sites and improved the conductivity, significantly improving the capacity performance of the electrode material.

[0045] See also Figure 11-13 As shown in the figure, in the three-electrode test system, 6 M potassium hydroxide solution was used as the electrolyte, the whole after the Ni3Fe@Fe3O4 active material was coated on the nickel foam was used as the working electrode, the platinum electrode was used as the counter electrode, and the silver / silver chloride electrode was used as the reference electrode. The electrochemical performance of the obtained material was tested; the prepared nickel nanowire aerogel has excellent electrochemical performance. At 1A g -1 At a current density of 1223 C g -1 The capacity is much higher than that of other control examples and activated carbon control examples in the invention (202 C g -1 ), when the current density increases 20 times, at 20 A g -1 At high current density, it can still maintain 442 C g -1 The capacity of the battery is 20 A g, showing excellent rate performance. -1 The negative electrode material was tested for cycle stability at a high current density of 1.5 GHz. After 5,000 cycles, it still achieved a capacitance retention rate of 69.8%, demonstrating excellent cycle stability. A series of electrochemical data showed that the introduction of dislocations and oxygen vacancies can significantly improve the actual energy storage capacity and stability of electrode materials, and can modify electrode materials without changing the electrode composition.

[0046] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made to the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for obtaining a high-performance supercapacitor negative electrode material by introducing dislocations and oxygen vacancies, characterized in that: The specific steps of this method are: S1. Reactant composition ratio and pretreatment: S1.

1. Select nickel source, iron source and complexing agent, and prepare mixed solution: The nickel source is anhydrous powdered nickel chloride NiCl2·6H2O; the iron source is anhydrous powdered ferrous sulfate FeSO4·7H2O; the complexing agent is white crystalline powdered sodium citrate C6H5Na3O7·2H2O; the method for preparing the complex solution is to place 0.523-1.046 g of nickel chloride powder, 0.611-1.223 g of ferrous sulfate powder and 0.441-1.323 g of sodium citrate powder in a glass container under dry and dust-free environment conditions, add 30 mL of ultrapure water to dissolve them, and place the base liquid on a magnetic stirrer and stir it with a rotor to mix it evenly to form a mixed solution for standby use, and stir continuously during the standby period; S1.2, prepare reducing agent solution: The reducing agent is a transparent liquid hydrazine hydrate N2H4·H2O. The reducing agent solution is prepared by adding 1-5 mL of hydrazine hydrate to 25-29 mL of ultrapure water to form a 2.6-13.3 vol% hydrazine hydrate reducing agent solution. The reducing agent solution is placed on a magnetic stirrer and stirred by a rotor to form a uniform reducing agent solution for standby use. Ultrasonic stirring is continued during the standby period. S1.3, pretreatment of the mixed solution and the reducing agent solution before reaction; The pretreatment includes adjusting the pH of the mixed solution and the reducing agent solution, deoxygenating and preheating; The pH adjustment method is to add 6 M potassium hydroxide (KOH) solution dropwise into the solution and repeatedly measure its pH value to adjust the pH value to 11-14; the deoxygenation method is to use argon gas to purge the mixed solution and the reducing agent solution for 0.25-1.5 h to remove the dissolved oxygen in the solution; the preheating method is to place the two solutions in a water bath and heat them to 60-100 ° C to preheat the solution; S1.4, the mixed solution is mixed with the reducing agent solution: In a dry and dust-free environment, quickly mix the mixed solution and the reducing agent solution in a beaker, stir quickly, add to the reaction device and seal; S2. Material preparation with controlled dislocation and oxygen vacancy introduction: S2.

1. Design of reaction device: The reaction generating device comprises an adjustable magnetic field generator, a water bath pot controlled by a constant temperature, an oxygen concentration tester, a reaction container, a sealing plug, an argon gas cylinder, an oxygen cylinder and a gas circuit system; The reaction container is placed in a thermostatically controlled water bath, and a sealing plug is used to seal the reaction container; an argon cylinder and an oxygen cylinder are used to introduce argon and oxygen into the reaction container through a gas path system, and an oxygen concentration tester is used to detect the oxygen concentration at the reaction interface in the reaction container. When the oxygen concentration at the interface reaches a predetermined value, the introduction of argon and oxygen is stopped and the reaction container is kept sealed; The magnetic field generator is used to provide a uniform magnetic field with magnetic lines parallel to the axis of the beaker and perpendicular to the surface of the solution in the reaction container, and the adjustable range is 0-1000 Gs; S2.2, Reaction environment parameter setting: The magnetic field generator provides a uniform magnetic field with a magnetic field strength B of 100-500 Gs, the temperature T of the constant temperature water bath is 60-100°C, and the interface gas phase is a mixed gas of argon and oxygen, wherein the volume percentage concentration of oxygen is 1-30%; S2.3, synthesis time: The synthesis time t is 0.5-3 h.

2. The method for obtaining a high-performance supercapacitor negative electrode material by introducing dislocations and oxygen vacancies according to claim 1, characterized in that: In step S1.1, 0.7843 g of nickel chloride powder, 0.9174 g of ferrous sulfate powder and 0.97 g of sodium citrate powder were added.

3. The method for obtaining a high-performance supercapacitor negative electrode material by introducing dislocations and oxygen vacancies according to claim 1, characterized in that: The reducing agent solution in step S1.2 is prepared by adding 4 mL of hydrazine hydrate to 26 mL of ultrapure water to prepare a 10.67 vol% hydrazine hydrate reducing agent solution.

4. The method for obtaining a high-performance supercapacitor negative electrode material by introducing dislocations and oxygen vacancies according to claim 1, characterized in that: In step S1.3, the pH value of the mixed solution and the reducing agent solution is adjusted to 13.3; the deoxygenation method is to use argon gas to purge the mixed solution and the reducing agent solution for 0.5h to remove the dissolved oxygen in the solution; The preheating step is to place the two solutions in a water bath and heat them to 80°C to preheat the solutions.

5. The method for obtaining a high-performance supercapacitor negative electrode material by introducing dislocations and oxygen vacancies according to claim 1, characterized in that: The synthesis environment parameter settings described in step S2.2 are: the magnetic field generator provides a uniform magnetic field with a magnetic field strength B of 300 Gs, the temperature T of the constant temperature water bath is 80°C, and the interface gas phase is a mixed gas of argon and oxygen, in which the volume percentage concentration of oxygen is 20%.

6. The method for obtaining a high-performance supercapacitor negative electrode material by introducing dislocations and oxygen vacancies according to claim 1, characterized in that: The method also includes post-treatment of S3 and Ni3Fe@Fe3O4 nanochains: S3.1, impurity cleaning; S3.

2. Drying.

7. The method for obtaining a high-performance supercapacitor negative electrode material by introducing dislocations and oxygen vacancies according to claim 6, characterized in that: The impurity cleaning in step S3.1 is to remove the magnetic field, centrifuge the product, and wash the product with water and ethanol respectively.

8. The method for obtaining a high-performance supercapacitor negative electrode material by introducing dislocations and oxygen vacancies according to claim 6, characterized in that: In step S3.2 drying, the process setting is to place the cleaned reaction product in a vacuum drying oven and dry it at 60-100 °C for 4-15 h to obtain Ni3Fe@Fe3O4 core-shell structure nanochains.

Citation Information

Cited By

  • Carbon-based capacitor electrode material, preparation method thereof and carbon-based capacitor

    CN120511156A